The promise of personalized peripheral nerve surgery - Bergmeister, Konstantin D.; Harhaus-Wähner, Leila (Journal of Personalized Medicine, 2024)
In peripheral nerve surgery, neuropathology and neural anatomy intersect with the complexities of injury and dysfunction [...]
Gesehen am 13.12.2024